Content Validity of the Occupational Therapy Anticipatory Awareness Test: A Functional Cognitive Assessment for Adults with Neurological Conditions - Danielle J. Mahoney; Lenin Grajo; Glen Gillen (Scholarworks @ WMU, 2021)
Background: The development of assessments that measure functional skills is a priority in the profession. Anticipatory awareness (i.e., the ability to anticipate the difficulties that might be experienced in daily life situations) is a critical skill in occupational performance. There is a lack of assessments measuring anticipatory awareness. The Occupational Therapy Anticipatory Awareness Test (OTAAT) is a performance-based assessment tool developed for individuals with neurological conditions. This study aimed to determine the tool's content validity. Methods: We recruited five experts to review whether the test items are essential for assessment and calculated the Content Validity Ratio (CVR). Open-ended questions allowed opportunity to provide feedback for tool revision. Results: Ten of the 14 items of the OTAAT were preserved. Eight out of the 14 items were rated as essential for measurement. Two of the 10 items were identified as useful but not essential. Following discussion, review of supporting literature, and analysis of qualitative feedback, the two emergent awareness items were kept. Four items were removed (strategy implementation and awareness of strategy use subdomains), as these were deemed not essential. Conclusion: This study determined preliminary content validity of the OTAAT. Future research should focus on establishing construct validity and test reliability.